2008
DOI: 10.1103/physreva.78.033810
|View full text |Cite
|
Sign up to set email alerts
|

Composition law for polarizers

Abstract: The polarization process when polarizers act on an optical field is studied. We give examples for two kinds of polarizers. The first kind presents an anisotropic absorption - as in a polaroid film - and the second one is based on total reflection at the interface with a birefringent medium. Using the Stokes vector representation, we determine explicitly the trajectories of the wave light polarization during the polarization process. We find that such trajectories are not always geodesics of the Poincar\'e sphe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…The generalized Malus' law is a classical subject in the theory of light polarization [5,7,[23][24][25][26], which is intimately connected with that of determining the gain given by a partial polarizer for partially polarized incident light.…”
Section: The Gain Of a Dichroic Device And The Generalized Malus' Lawmentioning
confidence: 99%
“…The generalized Malus' law is a classical subject in the theory of light polarization [5,7,[23][24][25][26], which is intimately connected with that of determining the gain given by a partial polarizer for partially polarized incident light.…”
Section: The Gain Of a Dichroic Device And The Generalized Malus' Lawmentioning
confidence: 99%
“…Vigoureux, who showed that the reflection coefficient of any stratified planar structure can be obtained using a complex generalization of Einstein's composition law for parallel relativistic velocities [8,10,11]. Recently, Lages et al [21] extended this quasi-relativistic result, showing that the composition law for polarizers is analogous with the composition law for noncolinear relativistic velocities. They also have determined the Wigner angle that corresponds to a sequence of two polarizers, as a natural consequence of the noncomutativity of this composition law.…”
mentioning
confidence: 92%
“…(3) Finally, I must stress that this vectorial composition rule that governs the interaction between a partially polarized SOP and a dichroic device-unlike the "quasirelativistic composition rule for two successive polarizers" [21]-does not imply a Wigner rotation per se.…”
mentioning
confidence: 99%
See 2 more Smart Citations